2014
DOI: 10.1162/jocn_a_00668
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Primary Visual Cortex Predicts Individual Differences in Fixation Duration during Text Reading

Abstract: In skilled reading, fixations are brief periods of time in which the eyes settle on words. E-Z Reader, a computational model of dynamic reading, posits that fixation durations are under real-time control of lexical processing. Lexical processing, in turn, requires efficient visual encoding. Here we tested the hypothesis that individual differences in fixation durations are related to individual differences in the efficiency of early visual encoding. To test this hypothesis, we recorded participants' eye moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
3
9
0
Order By: Relevance
“…The proportion of regressions (RegProp) also differed across the three conditions, F (2, 62) = 6.92, p < 0.005, with the NT condition producing more regressions than the average of the PW and the CS conditions, F (1, 31) = 8.01, p < 0.01, and a marginal difference between the PW and CS conditions, F (1, 31) = 4.0, p = 0.054. This general pattern of results in eye movements was similar to that reported in an analogous fMRI study (Henderson et al, 2014 ) and those obtained outside the scanner comparing natural and false-font texts (e.g., Henderson and Luke, 2012 , 2014 ; Luke and Henderson, 2013 ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The proportion of regressions (RegProp) also differed across the three conditions, F (2, 62) = 6.92, p < 0.005, with the NT condition producing more regressions than the average of the PW and the CS conditions, F (1, 31) = 8.01, p < 0.01, and a marginal difference between the PW and CS conditions, F (1, 31) = 4.0, p = 0.054. This general pattern of results in eye movements was similar to that reported in an analogous fMRI study (Henderson et al, 2014 ) and those obtained outside the scanner comparing natural and false-font texts (e.g., Henderson and Luke, 2012 , 2014 ; Luke and Henderson, 2013 ).…”
Section: Resultssupporting
confidence: 88%
“…Hillen et al ( 2013 ) also reported that a condition in which text was replaced by Landolt rings showed more activation in the right inferior parietal lobule relative to the conditions that used alphabetic characters, suggesting that “Landolt reading” similarly requires more attentional resources compared to the other conditions. In addition to the neural data, the behavioral eye movement data in the current experiment support this idea in that fixation durations in nonword reading were longer than those for normal reading, indicating that more effort is necessary for nonword reading than for normal reading (for similar findings, see Henderson and Luke, 2012 , 2014 ; Henderson et al, 2014 ). Another way to state this is that natural reading is highly automatized and therefore requires less attentional control than does consciously executing similar sequences of eye movements.…”
Section: Discussionsupporting
confidence: 76%
“…This interpretation is also consistent with the finding that fixation durations during natural reading are related to the anatomical structure of V1 (Henderson, Choi, & Luke, 2014). also found negative correlations between fixation durations and activations in the medial temporal lobe, indicating that less efficient scene processing might increase fixation durations.…”
Section: Functional Areas For Natural Reading and Scene Viewingsupporting
confidence: 90%
“…While the purpose of the present study was to explore the influence of individual differences on eye movements, our findings suggest that it should be possible to invert this approach and infer individual differences from eye-movement measures. Indeed, it should be possible to go further and associate particular properties of eye movements with specific regions or networks in the brain Henderson, Choi, Lowder, & Ferreira, 2016;Henderson, Choi, & Luke, 2014;. Eyemovement behaviors are highly stable over time, as reliable or more so than many standardized cognitive tests (Carter & Luke, 2018;.…”
Section: Clinical Implications Of the Current Findingsmentioning
confidence: 99%